Original papersCardiovascular responses to plyometric exercise are affected by workload in athletes - Arazi, Hamid; Asadi, Abbas; Mahdavi, Seyed Amir; Nasiri, Seyed Omid Mirfalah (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : With regard to blood pressure responses to plyometric exercise and decreasing blood pressure after exercise (post-exercise hypotension), the influence of different workloads of plyometric exercise on blood pressure is not clear. Aim: The purpose of this investigation was to examine the effects of a low, moderate and high workload of plyometric exercise on the post-exercise systolic (SBP) and diastolic blood pressure (DBP), heart rate (HR) and rate-pressure product (RPP) responses in athletes. Material and methods : Ten male athletes (age: 22.6 ±0.5 years; height: 178.2 ±3.3 cm; and body mass: 75.2 ±2.8 kg) underwent PE protocols involving 5 × 10 reps (Low Workload – LW), 10 × 10 reps (Moderate Workload – MW), and 15 × 10 reps (High Workload – HW) depth jump exercise from a 50-cm box in 3 non-consecutive days. After each exercise session, SBP, DBP and HR were measured every 10 min for a period of 70 min. Results : No significant differences were observed among post-exercise SBP and DBP when the protocols (LW, MW and HW) were compared. The MW and HW protocols showed greater increases in HR compared with LW. Also the HW indicated greater increases than LW in RPP at post-exercise (p < 0.05). Conclusions : All protocols increased SBP, HR and RPP responses at the 10th and 20th min of post-exercise. With regard to different workloads of plyometric exercise, HW condition indicated greater increases in HR and RPP and strength and conditioning professionals and athletes must keep in their mind that HW of plyometric exercise induces greater cardiovascular responses.